Meningkatkan Kesadaran Masyarakat Mengenai Pemanfaatan Teknologi Dalam Pemasaran Di UMKM Kelurahan Tanggung Kota Blitar - Sugeng Purwanto; Mulik Khabibah (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Digital marketing, which is the use of the internet and information technology in marketing, has experienced rapid growth along with the widespread use of the internet. Even, there are still a few MSME actors, especially in the Responsibility sub-district, who understand the optimal use of digital marketing. The Participatory Action Research (PAR) method is used to identify existing problems. The results of the study show that most MSME actors in the Respondent Village have a limited understanding of digital marketing. However, through socialization activities and digital marketing practices, MSME actors have succeeded in increasing their knowledge and skills in utilizing social media for marketing. This has a positive impact on increasing MSME sales and wider use of social media by MSME actors. This research contributes to building digital marketing awareness and capabilities for MSMEs, so that they can increase the competitiveness and sustainability of their businesses in the digital era.